Structure of oxidised silver (1 1 1) and (1 1 0) surfaces. Issue 5 (13th April 2017) - Isbill, Sara B.; Roy, Sharani; Keffer, David J.
Abstract: An exhaustive suite of classical molecular dynamics simulations is performed to investigate the stability of oxygen on silver (1 1 1) and (1 1 0) surfaces as a function of surface/subsurface location, binding site, fractional occupancy, and temperature. The ReaxFF potential is used to allow charge transfer between the oxygen and silver components. Comparison of the binding energies at various sites from ReaxFF and ab initio calculations reveals partial agreement between the two approaches. For many of the conditions sampled in the current study, we observe an initial state gives rise to a more disordered reconstruction, which is energetically more favourable. The driving force behind this reconstruction is largely an increase in the coordination of O by Ag, resulting in a more favourable binding site. The extent of reconstruction and atomic motion that initiates the reconstructive process is highly dependent on surface type, fractional occupancy, initially occupied site and temperature. For example, in the temperature range studied (77–500 K), on Ag(1 1 1) it is fractional occupancy that predominantly dictates the type and extent of reconstruction. However, on Ag(1 1 0) it is temperature rather than fractional coverage that is seen to have a more influential effect on the extent of surface reconstruction. These simulations clearly show that O atoms move from surface to subsurface sites, as has been observed experimentally.